2007
DOI: 10.1159/000106383
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of 13 Pediatric Patients with Dandy-Walker Syndrome

Abstract: We present our experience with the treatment of 13 patients with Dandy-Walker syndrome. The common presenting symptom and associated central nervous system anomaly were enlargement of head and occipital encephalocele, respectively. Eleven out of 13 patients were treated surgically after stabilization of systemic medical status. Two patients could not be operated because of poor medical condition. In 6 patients with an opened passage between posterior fossa cyst and lateral ventricle, cystoperitoneal shunt syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In this regard, prominent gyral development occurs after 25 weeks [ 38 ] while the gestational ages of fetuses with DWM at the time of MRI were mostly less than 25 weeks in this study. We also observed associated extracerebral anomalies, including congenital heart diseases, urinary tract malformations, and craniofacial abnormalities, as previously reported [ 39 , 40 ]. Fetuses with chromosomal abnormalities tend to have multiple anomalies; the results from this study indicate that fetuses presented with typical clinical demographics that are observed in children with DWM.…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, prominent gyral development occurs after 25 weeks [ 38 ] while the gestational ages of fetuses with DWM at the time of MRI were mostly less than 25 weeks in this study. We also observed associated extracerebral anomalies, including congenital heart diseases, urinary tract malformations, and craniofacial abnormalities, as previously reported [ 39 , 40 ]. Fetuses with chromosomal abnormalities tend to have multiple anomalies; the results from this study indicate that fetuses presented with typical clinical demographics that are observed in children with DWM.…”
Section: Discussionsupporting
confidence: 88%
“…There are various treatment options available for children with Dandy-Walker malformation, such as shunt placement, either ventriculoperitoneal, cystoperitoneal, or combined ventriculoperitoneal, and cystoperitoneal shunt, membrane excision, and endoscopic procedures. 4,5,13,14 Shunt placement in patients with Dandy-Walker malformation resulted in significant lower morbidity and mortality. 13 However, permanent shunting is not without complications.…”
Section: Discussionmentioning
confidence: 99%
“…In older children, symptoms of increased intracranial pressure such as irritability and vomiting and signs of cerebellar dysfunction such as gait disturbance and lack of muscle coordination may occur. 4,5 Other symptoms include cranial nerves dysfunction and abnormal breathing patterns. 6 Dandy-Walker malformation is frequently associated with disorders from other brain structures and with various extracranial abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In older children with Dandy-Walker syndrome, symptoms of increased intracranial pressure (ICP), including irritability and vomiting, and signs of cerebellar dysfunction, including gait disturbance and lack of muscle coordination, may occur [2]. In the present case, the patient had general muscular dystrophy and macrocephalus as well as craniofacial abnormalities such as micrognathia and cleft palate, which can make airway management challenging.…”
mentioning
confidence: 87%